Global trends in using the InVEST model suite and related research: A systematic review - Mukhopadhyay, Anirban; Hati, Jyoti Prakash; Acharyya, Rituparna; Pal, Indrajit; Tuladhar, Neshma; Habel, Michal (Ecohydrology & Hydrobiology, 2025)
The biggest global challenges in ecology today include the application of ecosystem services to map, visualise, and access relevant data to facilitate dialogue between scientists, decision-makers, and society at large. At least 350 publications were published in 2023 that used the InVEST model suite, which provides GIS-based solutions related to various ecosystem services. We have categorised the suite's 19 modules under eight distinct groups of ecosystem services. This work highlights the advantages of the InVEST model and focuses on comparing it with other ecological models. Our findings show that publications on applying the modules were mostly focused on Habitat Quality (29.5% of all articles), Annual Water Yield (22.3%), and Carbon Sequestration and Storage (19.9%), which can be argued as reflecting a trend towards research on climate change, with impacts such as habitat loss, sea level rise, flooding, and an increased number of extreme events having created a precarious situation for coastal populations. It can be observed in this review that scientists of Chinese descent have dominated the scene by applying various modules of the InVEST model with a specific focus on assessing various issues faced by ecosystem services of specific regions related to habitats, land use, water yield, and urbanisation. Finally, we have proposed an effective solution for how other models could be coupled with InVEST to provide the scientific community a greater, more comprehensive research output. We also found certain gaps after a thorough review of previous publications on InVEST. For example, InVEST currently needs a provision for biogeochemical cycle modelling and ecosystem-based management strategies.